Cost of surgical management of laparoscopically treated ectopic pregnancies at a tertiary referral hospital: A 10-year review of admission costs and contributing factors (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2025)
Background: Laparoscopic management is the gold standard for treating ectopic pregnancies (EP), but its cost limits its widespread use in developing nations. A 10-year period audit was conducted evaluating laparoscopically treated EPs at a tertiary referral hospital, focusing on admission cost and contributing factors.Methods: This was a retrospective observational study conducted at the Aga Khan University Hospital. All women admitted with surgically managed Eps were included. Analysis of data was done against a preset checklist. Descriptive statistics for continuous variables were computed and presented in tables and figures.Results: The adjusted admission cost for patients with surgically managed EP ranged from US $2 017 (KES 220 252) to US $ 6,326 (KES 690 828). The mean cost of admission was US $ 3 254 (KES 355 384; n=259). The following factors were significantly associated with an increased admission cost: increasing patient age (p=0.000), volume of hemoperitoneum(p=0.000) duration of surgery (p=0.003) and duration of hospital stay (p=0.000).Conclusion: The mean admission cost for surgically managed EP was similar to that in high-income countries. However, when adjusted for per capita gross domestic product, the cost was disproportionately high. No consistent decline in the mean annual cost was observed over the study period. Increasing patient age, hemoperitoneum volume, surgery duration, and duration of hospital stay all significantly impacted on the admission cost.